Company Business Strategy in Supermarkets in Makassar City - Idrus, Arifin (The International Journal of Education Management and Sociology, 2024)
This research aims to identify the strengths, weaknesses, opportunities, and threats of supermarkets. Develop the right business strategy for supermarkets. The research method uses a qualitative approach to describe phenomena that occur at the research location. Data collection techniques through interviews, observation, and documentation studies. Data analysis analyzes SWOT which starts by listing the indicators of strengths, weaknesses, opportunities, and business threats faced by Supermarkets. All indicators have their weighted values calculated after previously assigning weights and values to each indicator. The combination of weighted values of internal factors and external factors determines the strategic choices deemed appropriate for supermarkets. Results The high intensity of competition is very influential for supermarkets. Supermarket companies are required to continue to survive. SWOT analysis shows that supermarkets should use a growth strategy. The combination of market development strategy, market penetration strategy, and product development strategy is the right growth strategy for supermarkets.